Application of intelligent methods in energy efficiency enhancement of pump system: A review. (November 2022) - Gan, Xingcheng; Pei, Ji; Pavesi, Giorgio; Yuan, Shouqi; Wang, Wenjie
Abstract: Energy consumption around the world is growing at an alarming rate. That brings enormous pressure on energy production and environmental issues. Nowadays, energy efficiency enhancement strategies are considered the crucial approaches to release this problem. The pumps accounts for nearly 21% of the world electricity consumption of industrial motor-driven systems. Hence, much research focused on improving the energy efficiency of the pumps and their systems. According to the works of literature, the level of design of pumps for most applications is already extremely high while the system performance could be further improved by regulations, and the average energy savings potential achievable through pump system adjustments is about 30%. This paper focuses on the advanced characteristic modeling methods, and energy efficiency enhancement regulation approaches for the parallel pumping system. A comprehensive summary of traditional scheduling methods and advanced regulation methods based on computational intelligence has been made to provide insight for future research. Highlights: Identifies energy-saving potentials achievable through pump system optimization. Discusses advantages and requirements of different optimization methods. Compares traditional approaches and emerging intelligent methods. Provides recommendations for efficiency optimization of pump systems.